Impact of Type 1 Versus Type 2 Diabetes on Developing Herpes Zoster and Post-herpetic Neuralgia: A Population-based Cohort Study - Su-Ying Wen; Chao Ou-Yang; Catherine Chang; Chu-Chieh Chen; Hung-Yu Chang (Medical Journals Sweden, 2023)
Type 2 diabetes is associated with an increased risk of herpes zoster and postherpetic neuralgia. However, the association of type 1 diabetes with herpes zoster or postherpetic neuralgia remains unclear. This retrospective cohort study using Taiwan's Health Insurance Research Database included 199,566 patients with type 1 diabetes and 1,458,331 with type 2 diabetes, identified during the period 2000 to 2012. Patients with type 1 diabetes had a significantly higher risk of developing herpes zoster than those with type 2 diabetes (p < 0.001). Across all age groups, the impact of diabetes on herpes zoster was greater in type 1 than in type 2 diabetes. Patients with both type 1 and type 2 diabetes had a 1.45-fold higher risk of post-herpetic neuralgia than those without diabetes (hazard ratio 1.45, 95% confidence interval 1.28-1.65; hazard ratio 1.45, 95% confidence interval 1.37-1.52, respectively), and there was no difference between the 2 types of diabetes (hazard ratio 1.06; 95% confidence interval 0.93-1.21). The results recommend consideration of herpes zoster vaccination at an earlier age in patients with type 1 diabetes.